Assimilatory potential of helicoverpa armigera reared on host (chickpea) and nonhost (cassia tora) diets - Dawkar, Vishal V.; Chikate, Yojana R.; Gupta, Vidya S.; Slade, Susan E.; Giri, Ashok P. (Journal of Proteome Research, 2011)
Adaptation to plant allelochemicals is a crucial aspect of herbivore chemical ecology. To understand an insect ecology, we studied an effect of nonhost Cassia tora seed-based diet (Ct) on growth, development, and molecular responses in Helicoverpa armigera. We employed a comparative approach to investigate the proteomic differences in gut, hemolymph, and frass of H. armigera reared on a normal (chickpea seed-based, Cp) and Ct diet. In this study, a total of 46 proteins were identified by nano-LC-MS(E). Among them, 17 proteins were up-regulated and 29 proteins were down-regulated when larvae were exposed to the Ct diet. Database searches combined with GO analysis revealed that gut proteases engrossed in digestion, proteins crucial for immunity, adaptive responses to stress, and detoxification were down-regulated in the Ct fed larvae. Proteins identified in H. armigera hemolymph were found to be involved in defense mechanisms. Moreover, proteins found in frass of the Ct fed larvae were observed to participate in energy metabolism. Biochemical and quantitative real-time PCR analysis of selected candidate proteins showed differential gene expression patterns and corroborated with the proteomic data. Our results suggest that the Ct diet could alter expression of proteins related to digestion, absorption of nutrients, adaptation, defense mechanisms, and energy metabolism in H. armigera.
Keywords: adaptation; Cassia tora; Gene expression; Helicoverpa armigera; proteomics

Differential protease activity augments polyphagy in helicoverpa armigera - Chikate, Yojana R.; Tamhane, V. A.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Insect Molecular Biology, 2013)
Helicoverpa armigera (Lepidoptera: Noctuidae) and other polyphagous agricultural pests are extending their plant host range and emerging as serious agents in restraining crop productivity. Dynamic regulation, coupled with a diversity of digestive and detoxifying enzymes, play a crucial role in the adaptation of polyphagous insects. To investigate the functional intricacy of serine proteases in the development and polyphagy of H.armigera, we profiled the expression of eight trypsin-like and four chymotrypsin-like phylogenetically diverse mRNAs from different life stages of H.armigera reared on nutritionally distinct host plants. These analyses revealed diet- and stage-specific protease expression patterns. The trypsins expressed showed structural variations, which might result in differential substrate specificity and interaction with inhibitors. Protease profiles in the presence of inhibitors and their mass spectrometric analyses revealed insight into their differential activity. These findings emphasize the differential expression of serine proteases and their consequences for digestive physiology in promoting polyphagy in H.armigera.
Keywords: adaptation; chymotrypsin; Helicoverpa armigera; polyphagy; Trypsin

Molecular insights into resistance mechanisms of lepidopteran insect pests against toxicants - Dawkar, Vishal V.; Chikate, Yojana R.; Lomate, Purushottam R.; Dholakia, Bhushan B.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Proteome Research, 2013)
Insect pests remain a major reason for crop loss worldwide despite extensive use of chemical insecticides. More than B 50% of all insecticides are organophosphates, followed by synthetic pyrethroids, organochlorines, carbamates, and biopesticides, and their continued use may have many environmental, agricultural, medical, and socioeconomic issues. Importantly, only a countable number of insects have acquired the status of crop pests, mostly due to monoculture of crop plants and polyphagous nature of the insects. We focus on A adaptations of Lepidopteran insects to phytochemicals and synthetic pesticides in native and modern agricultural systems. Because of heavy use of chemical insecticides, a strong selection pressure is imposed on insect populations, resulting in the emergence of resistance against candidate compound(s). Current knowledge suggests that insects generally implement a three-tier system to overcome the effect of toxic compounds at physiological, biochemical, and genetic levels. Furthermore, we have discussed whether the adaptation to phytochemicals provides an advantage to the insect while encountering synthetic insecticide molecules. Specific metabolic pathways employed by insects to convert deterrents into less toxic forms or their removal from the system are highlighted. Using the proteomics approach, insect proteins interacting with insecticides can be identified, and their modification in resistant insects can be characterized. Also, systems biology studies can offer useful cues to decipher the molecular networks participating in the metabolism of detrimental compounds.
Keywords: field crops; insect-pests; insecticide; Lepidoptera; proteomics; resistance mechanisms

Expression of proteins involved in digestion and detoxification are regulated in helicoverpa armigera to cope up with chlorpyrifos insecticide - Dawkar, Vishal V.; Chikate, Yojana R.; More, Tushar H.; Gupta, Vidya S.; Giri, Ashok P. (Insect Science, 2016)
Helicoverpa armigera is a key pest in many vital crops, which is mainly controlled by chemical strategies. To manage this pest is becoming challenging due to its ability and evolution of resistance against insecticides. Further, its subsequent spread on nonhost plant is remarkable in recent times. Hence, decoding resistance mechanism against phytochemicals and synthetic insecticides is a major challenge. The present work describes that the digestion, defense and immunity related enzymes are associated with chlorpyrifos resistance in H. armigera. Proteomic analysis of H. armigera gut tissue upon feeding on chlorpyrifos containing diet (CH) and artificial diet (AD) using nano-liquid chromatography-mass spectrometry identified upregulated 23-proteins in CH fed larvae. Database searches combined with gene ontology analysis revealed that the identified gut proteins engrossed in digestion, proteins crucial for immunity, adaptive responses to stress, and detoxification. Biochemical and quantitative real-time polymerase chain reaction analysis of candidate proteins indicated that insects were struggling to get nutrients and energy in presence of CH, while at the same time endeavoring to metabolize chlorpyrifos. Moreover, we proposed a potential processing pathway of chlorpyrifos in H. armigera gut by examining the metabolites using gas chromatography-mass spectrometry. H. armigera exhibit a range of intriguing behavioral, morphological adaptations and resistance to insecticides by regulating expression of proteins involved in digestion and detoxification mechanisms to cope up with chlorpyrifos. In these contexts, as gut is a rich repository of biological information; profound analysis of gut tissues can give clues of detoxification and resistance mechanism in insects.
Keywords: chlorpyrifos; Helicoverpa armigera; insecticide resistance; proteomics; real-time PCR

RNAi of selected candidate genes interrupts growth and development of Helicoverpa armigera - Chikate, Yojana R.; Dawkar, Vishal V.; Barbole, Ranjit S.; Tilak, Priyadarshini V.; Gupta, Vidya S.; Giri, Ashok P. (Pesticide Biochemistry and Physiology, 2016)
Helicoverpa armigera is one of the major crop pests and is less amenable to current pest control approaches. RNA interference (RNAi) is emerging as a potent arsenal for the insect pest control over current methods. Here, we examined the effect on growth and development in H. armigera by targeting various enzymes/proteins such as proteases like trypsins (HaTry2, 3, 4 and 6), chymotrypsin (HaChy4) and cysteine protease like cathepsin (HaCATHL); glutathione S-transferases (HaGST1a, 6 and 8); esterases (HaAce4, HaJHE); catalase (HaCAT); super-oxide-dismutase (HaCu/ZnSOD); fatty acid binding protein (HaFabp) and chitin deacetylase (HaCda5b) through dsRNA approach. Significant downregulation of cognate mRNA expression and reduced activity of trypsin and GST-like enzyme were evident upon feeding candidate dsRNAs to the larvae. Among these, the highest mortality was observed in HaAce4 dsRNA fed larvae followed by HaJHE; HaCAT; HaCuZnSOD; HaFabp and HaTry3 whereas remaining ones showed relatively lower mortality. Furthermore, the dsRNA fed larvae showed significant reduction in the larval mass and abnormalities at the different stages of H. armigera development compared to their control diets. For example, malformed larvae, pupae and moth at a dose of 60 pg/day were evident in high number of individual insects fed on dsRNA containing diets. Moreover, the growth and development of insects and moths were retarded in dsRNA fed larvae. These findings might provide potential new candidates for designing effective dsRNA as pesticide in crop protection. (C) 2016 Elsevier Inc. All rights reserved.